Changes of 3-Alkyl-2-methoxypyrazines in Developing Cabernet Sauvignon (Vitis vinifera) and Zuoshanyi (Vitis amurensis Rupr.) Grapes from North China - Zhu, B.; Wu, Y.; Xu, X.; Pan, Q.; Duan, C. (South African Journal of Enology and Viticulture, 2016)
Changes in 3-alkyl-2-methoxypyrazines (MPs) in Cabernet Sauvignon (Vitis vinifera) and Zuoshanyi (Vitis amurensis Rupr.) grapes from different areas of North China were monitored throughout berry development in 2010. One kind of MP, 3-isobutyl-2-methoxypyrazine (IBMP), was detected in Cabernet Sauvignon grapes, and its content in grapes from Gaotai County was much higher than in those from the other two producing areas at the stages of véraison and maturity. Zuoshanyi grapes contained much more IBMP than Cabernet Sauvignon grapes, and an additional kind of MP, 3-isopropyl-2-methoxypyrazine (IPMP), was also detected in developing Zuoshanyi grapes. Abundant MPs might explain the stronger ‘green’ and ‘herbaceous’ characters in Zuoshanyi grapes. MPs accumulated in the early developmental stage in both Zuoshanyi and Cabernet Sauvignon grapes and rapidly decreased in the later stages. Delays in the time of harvest for Cabernet Sauvignon in Gaotai County and Zuoshanyi in Beijing are suggested in order to reduce MPs levels and the herbaceous character of these grapes.